Digital Transformative Resilience: Measuring Urban Governance Capacity to Improve Quality Public Services - Muhammad Kamil; Ayu Evita Sari; Rifki Muhammad (Universitas Muhammadiyah Tangerang, 2025)
Population growth, increasing needs, and community demands for the quality of digital-based public services through the Electronic-Based Government System (SPBE) are challenges that must be considered by the Malang City Government. An in-depth exploration of the government's capacity in the digital governance process needs to be carried out. The aim is to see the extent to which the government is able to meet the needs of the community and ensure the resilience of the digital transformation that has been developed. This research was conducted in Malang City because it has interesting conditions including population, several advantages and potentials, adequate infrastructure, government and community readiness, and SPBE index achievements. The research method used was qualitative analysis through a case study in line with Cresswell's qualitative design. The data triangulation method was applied to ensure data validity. Data analysis in qualitative research aims to minimize bias and misinterpretation when constructing arguments. Then the conclusion is drawn and the results are presented in the form of narrative information. The result is that government governance in implementing SPBE in Malang City has strived to have a capacity that is in accordance with the needs and demands of society. This means that the government seeks the resilience of digital transformation amid the challenges and threats that continue to arrive. This is evidenced through regulatory support that builds the realization of integrated SPBE, strengthening policies, governance, management, and also SPBE services. The SPBE achievement index continues to increase and public services are of higher quality. However, proactive, adaptive, responsive, and dynamic innovations need to be developed in the face of rapid social changes in society.Â Pertambahan jumlah penduduk, peningkatan kebutuhan, dan tuntutan masyarakat terhadap kualitas layanan publik berbasis digital melalui Sistem Pemerintahan Berbasis Elektronik (SPBE) menjadi tantangan yang wajib diperhatikan Pemerintah Kota Malang. Eksplorasi mendalam terhadap kapasitas pemerintah dalam proses tata kelola digital perlu dilakukan. Tujuannya adalah untuk melihat sejauh mana pemerintah mampu memenuhi kebutuhan masyarakat dan memastikan ketahanan transformasi digital yang telah dikembangkan. Penelitian ini dilakukan di Kota Malang karena memiliki kondisi yang menarik diantaranya jumlah penduduk, beberapa keunggulan dan potensi, infrastruktur yang memadai, kesiapan pemerintah dan masyarakat, serta capaian indeks SPBE. Metode penelitian yang digunakan adalah analisis kualitatif melalui studi kasus yang sejalan dengan desain kualitatif Cresswell. Metode triangulasi data diterapkan untuk memastikan keabsahan data. Analisis data dalam penelitian kualitatif bertujuan untuk meminimalkan bias dan kesalahan interpretasi saat mengkonstruksi argumen. Kemudian penarikan kesimpulan dilakukan dan hasilnya disajikan dalam bentuk informasi naratif Hasilnya tata kelola pemerintah dalam pengimplementasian SPBE di Kota Malang telah diupayakan memiliki kapasitas yang sesuai dengan kebutuhan dan tuntutan masyarakat. Artinya pemerintah mengupayakan ketahanan transformasi digital di tengah tantangan dan anacaman yang terus berdatangan. Hal ini dibuktikan melalui dukungan regulasi yang membangun perwujudan SPBE terintegrasi, penguatan kebijakan, tata kelola, manajemen, dan juga layanan SPBE. Indeks capaian SPBE pun terus meningkat dan layanan publik semakin berkualitas. Meskipun demikian inovasi proaktif, adaptif, responsif, dan juga dinamis perlu terus dikembangkan dalam menghadapai perubahan sosial masyarakat yang cukup pesat.